Adeno-associated viruses for efficient gene expression in the axolotl nervous system - Katharina Lust; Elly M. Tanaka (Proceedings of the National Academy of Sciences, 2025)
Axolotls are amphibian models for studying nervous system evolution, development, and regeneration. Tools to visualize and manipulate cells of the axolotl nervous system with high-efficiency, spatial and temporal precision are therefore greatly required. Recombinant adeno-associated viruses (AAVs) are frequently used for in vivo gene transfer of the nervous system but virus-mediated gene delivery to the axolotl nervous system has not yet been described. Here, we demonstrate the use of AAVs for efficient gene transfer within the axolotl brain, the spinal cord, and the retina. We show that serotypes AAV8, AAV9, and AAVPHP.eB are suitable viral vectors to infect both excitatory and inhibitory neuronal populations of the axolotl brain. We further use AAV9 to trace retrograde and anterograde projections between the retina and the brain and identify a cell population projecting from the brain to the retina. Together, our work establishes AAVs as a powerful tool to interrogate neuronal organization in the axolotl.